Office Da'wah Model in Building The Integrity of The State Civil Apparatus at The Ministry of Finance of The Republic of Indonesia - Bambang Heru Suhartono (Jurnal Syntax Transformation, 2023)
The national goal of the Indonesian nation as stated in the Preamble to the 1945 Constitution is to protect the entire Indonesian nation and all Indonesian bloodshed, promote general welfare, educate the nation's life, and participate in implementing world order based on independence, lasting peace, and social justice. In this study, qualitative Descriptive Analysis Methodology is used, which has natural characteristics (natural setting) as a source of direct, descriptive data, process is more important than results, analysis in qualitative research tends to be carried out by inductive analysis and meaning is essential. The office da'wah model involving mental coaching and structured character, DKM activities, capacity building, coaching mentoring counseling, and habituation of behavior in accordance with integrity, contributes positively to building the integrity of civil servants in the Ministry of Finance of the Republic of Indonesia. The office da'wah model has an important role in building the integrity of civil servants in the Ministry of Finance of the Republic of Indonesia. In this study, a high level of approval of activities and components related to office da'wah and building the integrity of civil servants.